Banana and papaya sauces as substitute for tomato sauce - Manoto, Herminia Z. (1959)
Artificial colorings (Neco strawberry-red and egg-yellow colors) and flavorings (citric acid and salt) were added to saba, of the variety Compressa (Musa paradisiaca Linn.) and to papaya (Carica papaya Linn.) to reach the imported tomato sauce in color, flavor and consistency. These factors were then evaluated subjectively by a panel of three judges. The specific gravity of the processed sauce was determined by the use of pyknometer and the pH by a Beckmann pH meter (model G).